Method for manufacturing easily adhesive film
By coating and heating the easily bonded composition on the transparent film base material, an easy bonded layer of water-based polyurethane with small emulsion particle size is formed, and a haze increase caused by the easy bonded layer in the prior art is solved, and an easy bonded film with high adhesion and high transparency is realized, which is suitable for improving the brightness and clarity of the image display device.
Patent Information
- Application Number
- CN202411112338.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-08-29
- Filing Date
- 2024-08-14
- Publication Date
- 2025-02-28
AI Technical Summary
In the prior art, although the easy-adhesive film having a polyurethane-based easy-adhesive layer on the transparent film base material has excellent adhesiveness, the formation of the easy-adhesive layer will cause an increase in haze, affecting the monomer transmittance of the polarizer and the sharpness of the display image.
The easy-adhesive layer is formed by coating the transparent film substrate with heat and removing the solvent while stretching in at least one direction. The easy-to-adhesive composition comprises an aqueous polyurethane having an emulsion particle size of 20 nm or less, and may include a crosslinking agent to improve adhesion.
High adhesion to the polarizer is achieved while maintaining high transparency and low haze. It is suitable for use as a polarizer protective film and improves the brightness and clarity of the image display device.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a method for producing an easily adhesive film having an easily adhesive layer on the surface of a transparent film substrate. Background Art
[0002] Liquid crystal display devices and organic EL display devices are widely used as various image display devices such as mobile devices, car navigation devices, personal computer displays, and televisions. Liquid crystal display devices are configured with polarizers on the visual recognition side surface of the liquid crystal unit according to their display principle. In a transmission-type liquid crystal display device, polarizers are configured on both sides of the liquid crystal unit. In an organic EL display device, in order to suppress external light from being reflected by a metal electrode (cathode) and looking like a mirror surface, a circular polarizer (typically a laminate of a polarizer and a 1 / 4 wavelength plate) is sometimes configured on the visual recognition side surface.
[0003] The polarizing plate generally has a transparent film or a polarizer protective film on one or both sides of the polarizer for the purpose of protecting the polarizer, etc. As the polarizer, a polyvinyl alcohol (PVA) film having iodine adsorbed thereon and oriented in molecules by stretching or the like is widely used.
[0004] As the polarizer protective film attached to the surface of the polarizer, from the aspect of excellent adhesion to the PVA type polarizer, cellulose-based films such as cellulose acetate are widely used. As the polarizer protective film, a film formed by resin materials such as acrylic acid, polyester, polycarbonate, cyclic polyolefin, etc. can also be used. The film formed by these resin materials is usually less adhesive to the polarizer than the cellulose-based film.
[0005] In order to improve the adhesion between the polarizer and the polarizer protective film, it is proposed to use an easy-adhesion film having an easy-adhesion layer on a transparent film substrate as the polarizer protective film. For example, Patent Document 1 discloses an easy-adhesion film having an easy-adhesion layer containing a polyurethane resin on the surface of a film substrate.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent No. 5354733 Summary of the invention
[0009] As image display devices become more refined, higher brightness and clear image quality are required, and optical films such as polarizers are required to have lower haze and higher transmittance. Although the easy-adhesion film having a polyurethane-based easy-adhesion layer on a transparent film substrate has excellent adhesion to the polarizer, the haze tends to increase due to the formation of the easy-adhesion layer, which may cause a decrease in the single transmittance of the polarizer and a decrease in the clarity of the displayed image due to light scattering.
[0010] In view of the above circumstances, an object of the present invention is to provide an easily adhesive film having excellent adhesion to a polarizer and high transparency.
[0011] Means for solving problems
[0012] The present invention relates to a method for producing an easy-adhesion film having an easy-adhesion layer on the surface of a transparent film substrate. The easy-adhesion layer is formed by coating an easy-adhesion composition on a transparent film substrate and heating the easy-adhesion composition to remove a solvent. When removing the solvent from the easy-adhesion composition, the transparent film substrate coated with the easy-adhesion composition can be stretched in at least one direction while being heated.
[0013] The easy-adhesion composition is an aqueous solution containing a water-based polyurethane having an emulsion particle size of 20 nm or less. The water-based polyurethane preferably does not have a cross-linked structure. The easy-adhesion composition may contain a cross-linking agent that can cross-link with the water-based polyurethane. The easy-adhesion composition may further contain microparticles.
[0014] The transparent film substrate may be an acrylic film. The thickness of the easy-adhesion layer may be 110 nm or more, or 280 nm or less.
[0015] Effects of the Invention
[0016] By forming the easy-adhesion layer using an easy-adhesion composition containing an aqueous polyurethane having a small emulsion particle size, an easy-adhesion film having low haze and high transparency can be obtained. The easy-adhesion film can be suitably used as a polarizer protective film. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 It is a cross-sectional view showing a configuration example of the easy-adhesion film.
[0018] Figure 2 It is a cross-sectional view showing a configuration example of a polarizing plate.
[0019] Description of Reference Numerals
[0020] 1 Easy-to-bond film
[0021] 11 Film substrate
[0022] 15 Easy bonding layer
[0023] 2 Transparent film
[0024] 5 Polarizer
[0025] 6, 7 Adhesive layer
[0026] 100 Polarizer DETAILED DESCRIPTION
[0027] Figure 1 Schematic cross-sectional view showing a configuration example of the easy adhesion film of the present invention. The easy adhesion film 1 includes an easy adhesion layer 15 on at least one surface of a film substrate 11. The easy adhesion layer may be provided on both surfaces of the film substrate.
[0028] As a usage form of the easy-adhesion film, a polarizer protective film can be mentioned. Figure 2 It is a cross-sectional view showing a configuration example of a polarizing plate including an easily adhesive film 1 as a polarizer protective film. The polarizing plate 100 includes the easily adhesive film 1 bonded to one surface of a polarizer 5 via an adhesive layer 6 . Figure 2 In the polarizing plate 100 shown, a transparent protective film 2 is bonded to the other surface of the polarizer 5 via an adhesive layer 7 .
[0029] [Film substrate]
[0030] As the film substrate 11, a transparent film is preferred. The total light transmittance of the transparent film substrate is preferably 80% or more, more preferably 85% or more, and further preferably 90% or more. As the resin material constituting the film substrate 11, acrylic resins, polyester resins, polycarbonate resins, polyolefin resins, cyclic polyolefin resins, polystyrene resins, polyamide resins, polyimide resins, etc. can be cited. In the case where the easy-adhesion film is used as an optically isotropic polarizer protective film, the resin material of the film substrate 11 is preferably an acrylic resin or a cyclic polyolefin resin, and particularly preferably an acrylic resin, from the aspect of small birefringence.
[0031] Examples of cyclic polyolefin resins include polynorbornene. Examples of commercially available cyclic polyolefin resins include ZEONOR and ZEONEX manufactured by ZEON Japan, ARTON manufactured by JSR, APEL manufactured by Mitsui Chemicals, and TOPASS manufactured by TOPAS ADVANCED POLYMERS. The cyclic polyolefin film preferably contains 50% by weight or more of the cyclic olefin resin.
[0032] Examples of acrylic resins include poly(meth)acrylates such as polymethyl methacrylate, methyl methacrylate-(meth)acrylic acid copolymers, methyl methacrylate-(meth)acrylic acid ester copolymers, methyl methacrylate-(meth)acrylic acid ester copolymers, methyl methacrylate-acrylate-(meth)acrylic acid copolymers, methyl (meth)acrylate-styrene copolymers (MS resins, etc.), and polymers having an alicyclic hydrocarbon group (e.g., methyl methacrylate-cyclohexyl methacrylate copolymers, methyl methacrylate-norbornyl (meth)acrylate copolymers, etc.).
[0033] In the present specification, "(meth)acrylic acid" means acrylic acid and / or methacrylic acid. The acrylic resin includes a resin containing acrylic acid or a derivative thereof as a monomer component and a resin containing methacrylic acid or a derivative thereof as a monomer component.
[0034] As the acrylic resin, the acrylic resin with glutaric anhydride structure described in Japanese Patent Publication No. 2006-283013, Japanese Patent Publication No. 2006-335902, Japanese Patent Publication No. 2006-274118, etc. can be used; and / or the acrylic resin with lactone ring structure described in Japanese Patent Publication No. 2000-230016, Japanese Patent Publication No. 2001-151814, Japanese Patent Publication No. 2002-120326, Japanese Patent Publication No. 2002-254544, Japanese Patent Publication No. 2005-146084, etc. The acrylic resin with glutaric anhydride structure and the acrylic resin with lactone ring structure have high heat resistance, high transparency and high mechanical strength, and are therefore suitable for manufacturing a polarizing plate with high polarization degree and excellent durability.
[0035] When the film substrate 11 is an acrylic film, the content of the acrylic resin in the film substrate is preferably 50% by weight or more, more preferably 60 to 98% by weight, and further preferably 70 to 97% by weight. The acrylic film may contain a thermoplastic resin other than the acrylic resin. For example, by blending other thermoplastic resins, the birefringence of the acrylic resin can be eliminated, and an acrylic film with excellent optical isotropy can be obtained. In addition, for the purpose of improving the mechanical strength of the film, a thermoplastic resin other than the acrylic resin may also be blended.
[0036] Examples of thermoplastic resins other than acrylic resins include olefin polymers, halogenated vinyl polymers, polystyrene, copolymers of styrene and acrylic monomers, polyesters, polyamides, polyacetals, polycarbonates, polyphenylene ethers, polyphenylene sulfides, polyetheretherketones, polysulfones, polyethersulfones, polyoxybenzylenes, polyamideimides, and rubber polymers.
[0037] The film substrate 11 may contain additives such as antioxidants, stabilizers, reinforcing materials, ultraviolet absorbers, flame retardants, antistatic agents, colorants, fillers, plasticizers, lubricants, and fillers. The resin material and additives may be mixed and prepared into a thermoplastic resin composition such as pellets before being formed into a film.
[0038] The thickness of the film substrate 11 is about 5 to 200 μm. From the viewpoints of mechanical strength, transparency, and handling properties, the thickness of the film substrate 11 is preferably 10 to 100 μm, and more preferably 15 to 60 μm.
[0039] The glass transition temperature Tg of the film substrate 11 is preferably 100° C. or higher, more preferably 110° C. or higher. When the film substrate 11 is an acrylic film, as described above, by using an acrylic resin having a glutaric anhydride structure or an acrylic resin having a lactone ring structure as the acrylic resin, the Tg of the acrylic film can be increased, thereby improving heat resistance. The upper limit of the Tg of the film substrate 11 is not particularly limited, but is preferably 170° C. or lower from the viewpoint of moldability.
[0040] As a method for producing the film substrate 11, a solution casting method, a melt extrusion method, a calendaring method, a compression molding method, etc. can be cited. The film substrate 11 can be any of an unstretched film and a stretched film. In the case where the film substrate 11 is an acrylic film, from the viewpoint of improving mechanical strength, the acrylic film is preferably a stretched film stretched in at least one direction, and is particularly preferably a biaxially stretched film. By compounding other thermoplastic resins in a manner to eliminate the birefringence of the acrylic resin, an acrylic film having low retardation even when stretched and excellent optical isotropy can be obtained.
[0041] [Easy-adhesive composition]
[0042] The easy-adhesion composition is applied to the surface of the film substrate 11, and the solvent is removed by heating to form the easy-adhesion layer 15. The easy-adhesion layer 15 can improve the adhesion to films such as polarizers, glass substrates, etc. In the present invention, an easy-adhesion composition containing an aqueous polyurethane having a predetermined emulsion particle size is used.
[0043] <Water-based polyurethane>
[0044] The easy-adhesion composition contains water-based polyurethane as a binder resin. The water-based polyurethane is obtained by emulsifying polyurethane. Polyurethane is typically a reaction product of a polyol and a polyisocyanate. As the polyol component, preferably a high molecular weight polyol such as polyacrylic polyol, polyester polyol, polyether polyol is used. As the polyisocyanate, aliphatic diisocyanate, alicyclic diisocyanate and aromatic diisocyanate can be used, and from the viewpoint of transparency, aliphatic diisocyanate or alicyclic diisocyanate is preferred.
[0045] The water-based polyurethane contained in the easy-adhesion composition preferably has a carboxyl group. By making the polyurethane have a carboxyl group, a cross-linked structure can be introduced, and there is a tendency to improve the adhesion between the easy-adhesion film 1 and the polarizer, etc. The polyurethane with a carboxyl group can be obtained by, for example, reacting a polyol and a polyisocyanate, and a chain extender with a free carboxyl group. As the chain extender with a free carboxyl group, dihydroxycarboxylic acid, dihydroxysuccinic acid, etc. can be listed. As the dihydroxycarboxylic acid, dihydroxyalkyl alkanoic acid such as dimethylol alkanoic acid (for example, dimethylol acetic acid, dimethylol butyric acid, dimethylol propionic acid, dimethylol butyric acid, dimethylol valeric acid) can be listed.
[0046] The number average molecular weight of the polyurethane is preferably 5,000 to 600,000, more preferably 10,000 to 400,000. The acid value of the polyurethane is preferably 10 to 50, more preferably 20 to 45.
[0047] Waterborne polyurethane can be reactive or non-reactive. Non-reactive waterborne polyurethane is an emulsion of polyurethane. Reactive waterborne polyurethane is formed by protecting the terminal isocyanate group of the reaction product (prepolymer) of polyol and polyisocyanate with a blocking agent and emulsifying it.
[0048] The emulsification method of the polyurethane is not particularly limited. The emulsification of the hydrophobic polyurethane is preferably carried out by using an emulsifier (surfactant) (forced emulsification). The polyurethane having a hydrophilic group such as a carboxyl group is self-emulsified by being dispersed in water. From the aspect of being able to reduce the particle size, a self-emulsifying water-based polyurethane is preferred.
[0049] The particle size of the emulsion of the water-based polyurethane is below 30 nm. By using a water-based polyurethane with a small emulsion particle size, the turbidity of the easy-adhesion composition is suppressed, and the mist of the easy-adhesion layer formed by coating and drying the easy-adhesion composition tends to decrease. Therefore, an easy-adhesion film with low mist and excellent transparency can be obtained.
[0050] From the viewpoint of low haze of the easy-adhesive composition and the easy-adhesive layer (easy-adhesive film), the particle size of the emulsion of the water-based polyurethane is more preferably below 25 nm, further preferably below 20 nm, and can be below 15 nm or below 10 nm. The particle size of the emulsion of the water-based polyurethane is usually above 1 nm, and can be above 3 nm or above 5 nm. The particle size of the emulsion of the water-based polyurethane is the median particle size (D50) of the particle size benchmark measured by the dynamic light scattering method using the aqueous dispersion as a sample.
[0051] Water-based polyurethane can have a cross-linked structure. By introducing the cross-linked structure in polyurethane, there is a tendency that the adhesion of the easy-bonding film to the polarizer etc. is improved. On the other hand, the emulsion particle size of the polyurethane with a cross-linked structure is large, so there is a tendency that the mist of the easy-bonding composition (solution) and the easy-bonding layer becomes higher. In addition, when the polyurethane has a cross-linked structure, it is easy to produce a viscosity rise and gelation of the solution, and there is a situation where the solution stability of the easy-bonding composition is poor.
[0052] <Crosslinking agent>
[0053] In the easy-adhesive composition, as a binder resin component, in addition to the water-based polyurethane, a crosslinking agent having a functional group that can react with the crosslinking functional group of the polyurethane can also be included. By including the crosslinking agent in the easy-adhesive composition, a crosslinking structure can be introduced into the polyurethane by heating when the easy-adhesive layer is formed. By using a polyurethane without a crosslinking structure as the water-based polyurethane and including the crosslinking agent in the easy-adhesive composition, the solution stability of the easy-adhesive composition can be improved and an easy-adhesive layer with excellent adhesion can be formed.
[0054] When polyurethane has carboxyl, use the cross-linking agent comprising amino, oxazoline group, epoxy group, carbodiimide group etc.Wherein, preferably have the cross-linking agent of oxazoline group.Oxazoline group is little with the reactivity of carboxyl at normal temperatures, therefore comprises the easy bonding composition of water-based polyurethane and oxazoline system cross-linking agent and is difficult for viscosity rise, gelation through time, and solution stability is excellent.
[0055] The cross-linking agent can be a low molecular compound or a polymer. From the aspect that the solubility in the water-based composition is high and the compatibility with the polyurethane is also excellent, as the cross-linking agent, a water-soluble acrylic acid polymer is preferably used. Particularly, when using an acrylic acid polymer with an oxazoline group as a cross-linking agent, there is a tendency that the adhesion of the films such as the easy-bonding film 1 and the polarizer is improved.
[0056] The amount of the crosslinking agent in the easy-adhesion composition is preferably 1 to 30 parts by weight, more preferably 3 to 25 parts by weight, and even more preferably 5 to 20 parts by weight, based on 100 parts by weight of the solid content of the aqueous polyurethane.
[0057] <Solvent>
[0058] The easy-adhesion composition containing water-based polyurethane as a binder resin is preferably an aqueous composition containing water as a solvent. The easy-adhesion composition may contain an organic solvent miscible with water as a solvent in addition to water.
[0059] <Microparticles>
[0060] The easy-adhesive composition may also contain microparticles in addition to water-based polyurethane and crosslinking agent as binder resins and water as solvent (and dispersion medium). By including microparticles in the easy-adhesive composition, fine concavo-convex is formed on the surface of the easy-adhesive layer 15, and the sliding property of the film is improved. Therefore, it is helpful to reduce the damage of the roller conveying of the easy-adhesive film 1 and suppress the blocking when it is wound into a roll.
[0061] From the viewpoint of forming a concavoconvex shape that helps to improve the sliding property, the particle size (average primary particle size) of the microparticles is preferably 10 nm or more, more preferably 15 nm or more, and further preferably 20 nm or more. The average primary particle size of the microparticles is preferably less than the thickness of the easy-adhesion layer. By making the particle size of the microparticles less than the thickness of the easy-adhesion layer, it is possible to suppress the microparticles from falling off the easy-adhesion layer. The particle size of the microparticles is preferably less than 250 nm, more preferably less than 200 nm. In addition, by making the average primary particle size of the microparticles less than the wavelength of visible light, the scattering of visible light at the interface between the binder resin and the microparticles can be suppressed. From the viewpoint of improving transparency, the particle size of the microparticles is preferably less than 100 nm, more preferably less than 80 nm, further preferably less than 60 nm, and particularly preferably less than 50 nm.
[0062] The microparticles may be any of inorganic microparticles and organic microparticles. From the perspective of excellent dispersibility and uniformity of particle size, inorganic microparticles are preferred as microparticles. As inorganic microparticles, inorganic oxides such as titanium dioxide, aluminum oxide, and zirconium oxide can be listed; calcium carbonate, talc, clay, calcined kaolin, calcined calcium silicate, hydrated calcium silicate, aluminum silicate, magnesium silicate, calcium phosphate, etc. can be listed. Among them, inorganic oxides are preferred. As organic microparticles, silicone resins, fluorine resins, acrylic resins, etc. can be listed. In order to suppress light scattering caused by microparticles, it is preferred that the refractive index difference between the binder resin (generally having a refractive index of about 1.5) and the microparticles is small. From the perspective of a small refractive index difference with the binder resin and excellent dispersibility, as microparticles, silica particles are preferred.
[0063] It is preferred to use fine particles with high water dispersibility in the aqueous easy-adhesion composition. An aqueous dispersion of fine particles may also be blended into the composition. In order to improve the dispersibility of the fine particles, an alkaline component such as amine or ammonia may be added to make the easy-adhesion composition weakly alkaline.
[0064] As water-dispersible silica particles, colloidal silica is preferably used. As colloidal silica, commercially available products such as Quartron PL series manufactured by Fuso Chemical Industry Co., Ltd., SNOWTEX series manufactured by Nissan Chemical Industry Co., Ltd., AERODISP series and AEROSIL series manufactured by Nippon AEROSIL Co., Ltd., and SEAHOSTAR KE series manufactured by Nippon Shokubai Co., Ltd. can be used.
[0065] From the viewpoint of improving the slip of the easy-adhesive film 1 by forming concavoconvex on the surface of the easy-adhesive layer 15, the content of the microparticles is preferably 3% by weight or more, more preferably 5% by weight or more relative to the total solid content of the easy-adhesive composition. In particular, when the thickness of the easy-adhesive layer 15 is small, it is preferred to increase the amount of microparticles per unit area (number density) by increasing the content of the microparticles, so as to uniformly form concavoconvex in the surface of the easy-adhesive layer 15. The content of the microparticles in the easy-adhesive layer 15 is preferably 8% by weight or more, more preferably 10% by weight or more, and further preferably 12% by weight or more. When the content of the microparticles in the easy-adhesive layer 15 is too large, it sometimes leads to a decrease in optical properties caused by an increase in light scattering at the interface between the binder resin and the microparticles. In addition, as the content of the microparticles increases, the relative content of the binder resin decreases, so sometimes the adhesion of the easy-adhesive layer decreases. Therefore, the content of the microparticles is preferably 50% by weight or less, more preferably 40% by weight or less, and further preferably 30% by weight or less relative to the total solid content of the easy-adhesive composition.
[0066] <Other ingredients>
[0067] The easy-adhesive composition may contain a resin component other than the water-based polyurethane as a binder resin. From the viewpoint of ensuring the adhesion and transparency of the easy-adhesive film, the ratio of the polyurethane resin (including a cross-linking agent that can cross-link with the polyurethane) in the binder resin component is preferably 50% by weight or more, more preferably 70% by weight or more, more preferably 80% by weight or more, and further preferably 90% by weight or more, and can be 95% by weight or more, 98% by weight or more, 99% by weight or more, or 100% by weight.
[0068] The easy-adhesion composition may contain alkaline components such as ammonia and amines for the purpose of improving the dispersibility of the particles. The easy-adhesion composition may contain catalysts such as crosslinking accelerators, antioxidants, free radical scavengers, ultraviolet absorbers, leveling agents, anti-blocking agents, antistatic agents, dispersion stabilizers, defoamers, thickeners, dispersants, surfactants, lubricants and other additives.
[0069] <Preparation of Easy Adhesion Composition>
[0070] The easy-adhesive composition is prepared by dissolving and dispersing the aqueous polyurethane as a binder resin and, if necessary, a crosslinking agent, microparticles, an alkali component, and other various additives in water (or an aqueous solvent with water as the main component) as a solvent. From the viewpoints of the stability and coating properties of the solution, the concentration of the solid component (non-volatile component) in the easy-adhesive composition is preferably 1 to 30% by weight, more preferably 3 to 20% by weight, and further preferably 5 to 15% by weight.
[0071] The solid content concentration of the water-based polyurethane in the easy-adhesive composition is preferably 1 to 20% by weight, more preferably 2 to 15% by weight, further preferably 3 to 12% by weight, and can be 4 to 10% by weight. If the concentration of the water-based polyurethane is too low, it is difficult to increase the thickness of the easy-adhesive layer, and sometimes the adhesion to the polarizer and the like becomes insufficient. On the other hand, if the concentration of the water-based polyurethane is too high, it may become the cause of the increase in the haze of the easy-adhesive film caused by the decrease in transparency (cloudiness) of the solution and the decrease in the stability of the solution.
[0072] From the viewpoint of coating properties, the solution viscosity of the easy-adhesion composition at a temperature of 25° C. is preferably 1 to 100 cP, more preferably 2 to 50 cP, further preferably 3 to 30 cP, and may be 4 to 20 cP or 5 to 15 cP. The rate of change in viscosity of the easy-adhesion composition when left at room temperature for 24 hours after preparation is preferably within ±100%, more preferably within ±50%, further preferably within ±30%.
[0073] The haze of the easy-adhesive composition is preferably 40% or less when measured using a measuring cell with an optical path length of 1 cm. The smaller the particle size of the aqueous polyurethane emulsion as the binder resin, the smaller the haze of the easy-adhesive composition, and there is a tendency for the haze of the easy-adhesive film to become smaller. The haze of the easy-adhesive composition is more preferably 30% or less, more preferably 25% or less, and can be 20% or less or 15% or less. The haze of the easy-adhesive composition is greater than 0, and can be 1% or more, 3% or more, 5% or more, or 7% or more.
[0074] [Formation of Easy Adhesion Layer]
[0075] The easily adhesive film 1 including the easily adhesive layer 15 on the film substrate 11 is formed by applying the easily adhesive composition on the film substrate 11 and heating the easily adhesive composition on the film substrate to remove the solvent.
[0076] Before applying the easy-adhesive composition on the film substrate 11, the film substrate may be subjected to a surface treatment. By performing the surface treatment, the wetting tension of the film substrate can be adjusted to improve the adhesion with the easy-adhesive layer 15. As surface treatment, corona treatment, plasma treatment, ozone blowing, ultraviolet irradiation, flame treatment, chemical reagent treatment, etc. can be listed. Among them, corona treatment or plasma treatment is preferred.
[0077] As the coating method of the easy bonding composition, rod coating, roller coating, gravure coating, rod coating, slit hole coating, curtain coating, injection coating, etc. can be listed. By heating the easy bonding composition after coating, removing the solvent, thus forming the easy bonding layer 15. It is also possible to heat the precursor material reaction of the binder resin and solidify. For example, when the easy bonding composition includes a crosslinking agent, the crosslinking reaction can be promoted by heating.
[0078] The heating temperature during the formation of the easy-adhesion layer is, for example, about 50 to 200° C. From the viewpoint of promoting the curing reaction of the resin component in the easy-adhesion composition, the heating temperature is preferably 100° C. or higher, more preferably 120° C. or higher, further preferably 130° C. or higher, and particularly preferably 135° C. or higher. When the easy-adhesion composition contains an alkali component such as amine or ammonia, the heating temperature is preferably higher than the boiling point of the alkali component from the viewpoint of effectively volatilizing and removing the alkali component and reducing the amount of residual alkali.
[0079] The easy-adhesive layer can also be formed in the manufacturing process of the film substrate. In addition, the easy-adhesive layer can also be formed by heating during the formation of the film substrate. For example, in the case where the film substrate is a stretched film, the easy-adhesive composition can be applied to the surface of the film before stretching or after longitudinal stretching, and the solvent can be dried and the resin can be cured by heating during transverse stretching or simultaneous biaxial stretching based on a tenter.
[0080] When the film substrate is stretched after the coating easy bonding composition, from the viewpoint of suppressing the easy bonding layer to produce the undesirable conditions such as cracks, the stretching ratio is preferably less than 5 times, more preferably less than 4 times, further preferably less than 3 times, and particularly preferably less than 2.5 times. The lower limit of the stretching ratio is not particularly limited, and from the viewpoint of improving film strength, the stretching ratio is preferably more than 1.3 times, more preferably more than 1.5 times. In the case where the film substrate is an acrylic film, from the viewpoint of improving film strength, preferably in the conveying direction (MD) and the width direction (TD), respectively, stretching is implemented with the above-mentioned stretching ratio.
[0081] In the case of biaxial stretching of a film substrate, biaxial stretching can be biaxial stretching one by one or biaxial stretching at the same time. In addition, oblique stretching can also be performed. In the case of biaxial stretching one by one, after the film is stretched in one direction (MD) by roller stretching as described above, an easy bonding composition is applied to the film, and the easy bonding composition is heated when stretched based on a tenter.
[0082] By adjusting the solid content concentration and coating thickness of the adhesive composition, the thickness of the adhesive layer 15 can be adjusted. When the film substrate is stretched after coating the adhesive composition, the thickness of the adhesive layer 15 can also be adjusted by the stretching ratio.
[0083] The thickness of the easy bonding layer is not particularly limited, and is usually about 10nm to 2μm. From the viewpoint of improving the adhesion to the polarizer, etc., the thickness of the easy bonding layer is preferably more than 110nm, more preferably more than 130nm, and can be more than 140nm or more than 150nm. From the viewpoint of suppressing uneven bonding when bonding with the polarizer, etc., and suppressing the generation of stripe-shaped unevenness when the polarizer is exposed to a humidified environment, the thickness of the easy bonding layer is preferably less than 500nm, more preferably less than 300nm, and further preferably less than 280nm, and can be less than 250nm or less than 230nm.
[0084] The total light transmittance of the easy-adhesion film is preferably 85% or more, more preferably 90% or more, and can be 91% or more or 92% or more. The haze of the easy-adhesion film is preferably 1.0% or less, more preferably 0.5% or less, and can be 0.3% or less or 0.2% or less. By using a highly transparent film such as an acrylic film as the film substrate 11 and using a water-based polyurethane with a small emulsion particle size as the binder resin of the easy-adhesion layer, an easy-adhesion film having an easy-adhesion layer with excellent adhesion to a polarizer and the like and high transparency can be obtained.
[0085] [Polarizing plate]
[0086] As described above, the easy-adhesion film can be used as a polarizer protective film of the polarizing plate. The polarizing plate may have a polarizer protective film only on one side of the polarizer, or may have a polarizer protective film on one side of the polarizer. Figure 2 As shown, the polarizer 5 is provided with polarizer protective films on both sides. By laminating the above-mentioned easy-adhesive film as the polarizer protective film on one side of the polarizer, a polarizer having a transparent protective film only on one side of the polarizer is formed. The polarizer having polarizer protective films on both sides of the polarizer only needs to have the above-mentioned easy-adhesive film laminating on at least one side of the polarizer. The polarizer can also have the above-mentioned easy-adhesive film laminating on both sides of the polarizer. The polarizer 5 and the easy-adhesive film 1 are laminating with the aid of an adhesive layer 6.
[0087] <Polarizer>
[0088] As the polarizer 5, a polyvinyl alcohol (PVA) polarizer can be used, which is formed by adsorbing a dichroic substance such as iodine or a dichroic dye onto a polyvinyl alcohol film such as polyvinyl alcohol or partially formalized polyvinyl alcohol and orienting the film in one direction. For example, a PVA polarizer can be obtained by dyeing a polyvinyl alcohol film with iodine and stretching the film.
[0089] <Adhesive>
[0090] The adhesive layer 6 used in laminating the polarizer 5 and the easy-adhesion film 1 is not particularly limited in material as long as it is optically transparent, and examples thereof include epoxy resins, silicone resins, acrylic resins, polyurethanes, polyamides, polyethers, polyvinyl alcohols, and the like. The thickness of the adhesive layer 6 is, for example, about 0.01 to 20 μm, and is appropriately set according to the type of adherend, the material of the adhesive, and the like. In the case of using a curing adhesive that exhibits adhesion through a cross-linking reaction after coating, the thickness of the adhesive layer 6 is preferably 0.01 to 5 μm, and more preferably 0.03 to 3 μm.
[0091] As the adhesive, various adhesives are used, such as water-based adhesives, solvent-based adhesives, hot melt adhesives, active energy ray-curable adhesives, etc. Among them, water-based adhesives or active energy ray-curable adhesives are preferred because the thickness of the adhesive layer can be reduced.
[0092] <Production of polarizing plate>
[0093] The polarizing plate is manufactured by bonding the easy-adhesive film 1 to one side of the polarizer 5 via the adhesive layer 6. The easy-adhesive layer-forming side of the easy-adhesive film 1 can be bonded to the polarizer 5 via the adhesive layer, and the easy-adhesive layer-non-forming side can be bonded to the polarizer 5 via the adhesive layer. Figure 2 As shown, by laminating the polarizer 5 on the easy-adhesive layer 15 forming surface of the easy-adhesive film 1 with the help of the adhesive layer 6, a polarizing plate having high adhesion between the polarizer and the polarizer protective film (easy-adhesive film 1), excellent mechanical strength and durability can be obtained. In the case where the non-forming surface of the easy-adhesive layer is laminated to the polarizer with the help of the adhesive layer, the adhesion with other films, adhesive layers, glass substrates, etc. provided on the easy-adhesive film can be improved.
[0094] In the lamination of the polarizer 5 and the easy-adhesion film 1, it is preferred that after the adhesive composition is applied to either or both of the polarizer 5 and the easy-adhesion film 1, the polarizer 5 and the easy-adhesion film 1 are laminated using a roll laminator or the like to cure the adhesive. As a method for applying the adhesive composition to the polarizer 5 and / or the easy-adhesion film 1, a roller method, a spray method, a dipping method, etc. can be cited. Before the adhesive composition is applied to the surface of the polarizer 5 and / or the easy-adhesion film 1, a surface treatment such as a corona treatment, a plasma treatment, a saponification treatment, etc. can be performed.
[0095] After the polarizer 5 and the easy-adhesion film 1 are attached, the adhesive is cured according to the type of the adhesive, thereby forming an adhesive layer 6. When a water-based adhesive is used, the adhesive is cured by heating and drying. When an active energy ray-curable adhesive is used, the adhesive is cured by irradiation with active energy rays such as electron beams and ultraviolet rays.
[0096] <Transparent protective film>
[0097] A transparent protective film 2 may also be attached to the other side of the polarizer 5 by means of an adhesive layer 7. As the transparent protective film 2, any appropriate transparent film may be used. The thickness of the transparent protective film 2 is about 5 to 200 μm. From the viewpoints of mechanical strength, transparency, and operability, the thickness of the transparent protective film 2 is preferably 10 to 100 μm, and more preferably 15 to 60 μm. The thickness of the easy-adhesion film 1 and the transparent protective film 2 may be the same or different.
[0098] Examples of materials for forming the transparent protective film 2 include polyesters such as polyethylene terephthalate (PET), polybutylene terephthalate (PBT), and polyethylene naphthalate (PEN); cellulose polymers such as cellulose diacetate and cellulose triacetate; styrene polymers such as polystyrene and acrylonitrile-styrene copolymer; cyclic polyolefins such as polynorbornene; and polycarbonate.
[0099] The transparent protective film 2 may include an easy-adhesion layer (not shown) on the surface to be bonded to the polarizer 5. The transparent protective film 2 may be provided with an easy-adhesion layer similar to the easy-adhesion layer 15 of the easy-adhesion film 1.
[0100] As the adhesive layer 7 used for bonding the polarizer 5 and the transparent protective film 2, various adhesive layers such as water-based adhesives, solvent-based adhesives, hot melt adhesives, and active energy ray-curable adhesives can be used. The adhesive layer 6 and the adhesive layer 7 can use the same adhesive composition.
[0101] <Uses of Polarizing Plates>
[0102] Polarizer can be used as a component of image display devices such as liquid crystal display devices and organic EL display devices. By attaching the polarizer to the surface of image display units such as liquid crystal cells and organic EL cells, an image display device can be formed. The formation of the liquid crystal display device is formed by appropriately assembling the liquid crystal cell and the polarizer, and the components such as the lighting system as required and loading them into the drive circuit, etc. In the organic EL display device, by attaching the circular polarizer formed by combining the polarizer of the present invention with a phase difference film (typically a 1 / 4 wavelength plate) on the surface of the organic EL cell, the re-emission of reflected light of external light caused by metal electrodes, etc. can be reduced, and visual recognition can be improved.
[0103] The easy-adhesion film has high transparency, so the polarizing plate including the easy-adhesion film as a polarizer protective film has high single body transmittance and low haze. The polarizing plate can contribute to higher brightness and improved clarity of image display devices.
[0104] Example
[0105] The present invention will be described in more detail below with reference to Examples, but the present invention is not limited to these Examples. In the following, "%" of concentration is represented by weight % unless otherwise specified.
[0106] [Example 1]
[0107] <Preparation of Easy Adhesion Composition>
[0108] 20.0 parts by weight of a water-based polyurethane having a solid content of 22% (HYDRAN AP-40F manufactured by DIC, emulsion particle size: 5 to 10 nm), 3.0 parts by weight of an aqueous oxazoline-containing polymer solution having a solid content of 25% (EPOCROS WS-700 manufactured by Nippon Shokubai), 5.0 parts by weight of a 20% aqueous dispersion of colloidal silica having an average primary particle size of 35 nm (Quartron PL-3 manufactured by Fuso Chemical Industries, Ltd.), 3.0 parts by weight of 1% ammonia water, and 69.0 parts by weight of pure water were mixed to prepare an easy-adhesion composition 1 (solid content concentration: 6.2%, ratio of polyurethane to total solid content: 71.5%, solid content concentration of polyurethane: 4.4%).
[0109] <Formation of an Adhesive Layer on Acrylic Film>
[0110] An easy-to-adhesive film is prepared using a film manufacturing device equipped with a melt extrusion film-making device, a gravure coater, a tenter-type simultaneous biaxial stretching device and a winding device. As an acrylic resin, pellets of the same imidized MS resin (glass transition temperature: 120°C) used in the preparation of the "transparent protective film 1A" described in the embodiment of Japanese Patent Publication No. 2017-26939 are used. The acrylic resin is melt-extruded from a T-die, and a film is formed with a thickness of 160 μm. The above-mentioned easy-to-adhesive composition is applied to one side of the film with a wet thickness of about 6.5 μm using a gravure coater, and the film is stretched to 2 times in the length direction (MD) and the width direction (TD) using a simultaneous biaxial stretching tenter in a heating furnace at a temperature of 140°C, to obtain an easy-to-adhesive film having an easy-to-adhesive layer of 200 nm in thickness on one side of an acrylic film of 40 μm in thickness.
[0111] [Comparative Example 1]
[0112] 6.5 parts by weight of a water-based polyurethane having a solid content of 34% ("SUPERFLEX 210R" manufactured by Daiichi Kogyo Seiyaku, emulsion particle size: 40 nm), 1.5 parts by weight of an aqueous solution of an oxazoline-containing polymer ("EPOCROS WS-700" manufactured by Nippon Shokubai), 2.5 parts by weight of a colloidal silica aqueous dispersion ("Quartron PL-3" manufactured by Fuso Chemical Industries), 3.0 parts by weight of 1% ammonia water, and 86.5 parts by weight of pure water were mixed to prepare an easy-adhesion composition 2 (solid content concentration: 3.1%, ratio of polyurethane to total solid content: 71.6%, solid content concentration of polyurethane: 2.2%). Using this easy-adhesion composition, an easy-adhesion film having an easy-adhesion layer having a thickness of 100 nm on an acrylic film was prepared in the same manner as in Example 1.
[0113] [Comparative Example 2]
[0114] The amount of water-based polyurethane, oxazoline-containing polymer aqueous solution and colloidal silica aqueous dispersion was set to twice that of Comparative Example 1, and the amount of pure water was changed to 76 parts by weight to prepare an easy-adhesion composition 3 (solid content concentration: 6.2%, ratio of polyurethane to total solid content: 71.6%, solid content concentration of polyurethane: 4.4%). Using this easy-adhesion composition, an easy-adhesion film having an easy-adhesion layer with a thickness of 200 nm on an acrylic film was prepared in the same manner as in Example 1.
[0115] [Comparative Examples 3 to 6]
[0116] Easy-adhesive compositions 4 to 7 (solid content concentration: 6.2%, ratio of polyurethane to total solid content: 71.6%) were prepared in the same manner as in Comparative Example 2 except that the type and blending amount of the aqueous polyurethane and the blending amount of pure water were changed, and easy-adhesive films having an easy-adhesive layer with a thickness of 200 nm on an acrylic film were prepared.
[0117] The following water-based polyurethanes were used in Comparative Examples 3 to 6. It should be noted that "HYDRAN RCP-A-220" used in Comparative Example 6 (easy-adhesion composition 7) is a cross-linked polyurethane, and the polyurethanes used in the other examples are polyurethanes that do not have a cross-linked structure.
[0118] Comparative Example 3 (easy-adhesion composition 4): "TAKELAC W-6010" manufactured by Mitsui Chemicals, emulsion particle size: 60 nm
[0119] Comparative Example 4 (easy-adhesion composition 5): "TAKELAC W-605" manufactured by Mitsui Chemicals, emulsion particle size: 80 nm
[0120] Comparative Example 5 (easy-adhesion composition 6): "TAKELAC W-6061" manufactured by Mitsui Chemicals, emulsion particle size: 100 nm
[0121] Comparative Example 6 (easy-adhesive composition 7): DIC "HYDRAN RCP-A-220", emulsion particle size: 100 nm
[0122] [evaluate]
[0123] <Evaluation of Easy Adhesion Composition (Solution)>
[0124] (Viscosity)
[0125] For the easily adhesive compositions 1 to 7 used for preparing the easily adhesive films of Examples and Comparative Examples, the solution viscosity was measured using a B-type viscometer at 25° C. immediately after preparation. Then, the solution was left to stand at room temperature (25° C.) for 24 hours and the viscosity was measured again to evaluate the viscosity change.
[0126] (Haze of solution)
[0127] The easily adhesive composition immediately after preparation was filled in a measuring cell having an optical path length of 1 cm, and the haze of the solution was measured using a haze meter ("NDH-8000" manufactured by Nippon Denshoku Industries).
[0128] <Evaluation of Easy Adhesion Film>
[0129] (Haze and total light transmittance)
[0130] The haze and total light transmittance of the easy-adhesion film were measured using a haze meter ("NDH-8000" manufactured by Nippon Denshoku Industries).
[0131] (Adhesion strength of easy-adhesion layer)
[0132] A polarizing plate was prepared by attaching an easy-adhesive film to one side of a 18 μm thick polyvinyl alcohol polarizer and attaching a biaxially stretched cyclic polyolefin film (ZEONOR FILM ZF-14 manufactured by ZEON Japan) to the other side. A photo-radical curable adhesive (containing 40 parts by weight of N-hydroxyethyl acrylamide and 60 parts by weight of acryloyl morpholine as curing components) was applied to the easy-adhesive layer-forming surface of the easy-adhesive film and the surface of the ZEONOR FILM at a thickness of about 1 μm, attached to the polarizer using a roll laminator, and irradiated with a cumulative light dose of 1000 mJ / cm 2 The ultraviolet rays cure the adhesive.
[0133] The polarizer was cut into a size of 200 mm parallel to the stretching direction of the polarizer (absorption axis direction) and 15 mm in the orthogonal direction (transmission axis direction). After cutting an incision between the easy-adhesive film and the polarizer with a cutting knife, the surface of the ZEONORFILM side of the polarizer was attached to the glass plate. A peeling test was performed using a tensile compression tester (Minebea "TG-1kN") at a peeling angle of 90° and a peeling speed of 1000 mm / min to measure the adhesion between the polarizer and the easy-adhesive film. The adhesion strength was 0 for a bonding strength of 2.0 N / 20 mm or more, and × for a bonding strength of less than 2.0 N / 20 mm.
[0134] [Evaluation results]
[0135] Table 1 shows the evaluation results of the easily adhesive compositions and easily adhesive films of Examples and Comparative Examples.
[0136] [Table 1]
[0137]
[0138] The solution of Example 1 (easy-adhesive composition 1) using an aqueous polyurethane with a small emulsion particle size has low haze, low viscosity, no viscosity change over time, and excellent solution stability. The easy-adhesive film of Example 1 has high transparency and excellent adhesion to a polarizer.
[0139] Comparative Example 2 (easy adhesion composition 3) using an aqueous polyurethane having an emulsion particle size of 40 nm or more has good solution stability, but the solution has high haze, and the easy adhesion film produced using the easy adhesion composition has high haze and poor transparency compared with Example 1. Comparative Example 1 (easy adhesion composition 2) in which the solid content concentration of the solution is halved has a smaller solution haze than Comparative Example 2, and the transparency of the easy adhesion film is improved, but the transparency is poor compared with Example 1. In Comparative Example 1, the thickness of the easy adhesion layer is small, so the adhesion between the easy adhesion film and the polarizer is insufficient.
[0140] In Comparative Examples 3 to 6 (easy-adhesive compositions 4 to 7) using water-based polyurethanes having a larger emulsion particle size than that of Comparative Example 2, it was observed that the haze of the easy-adhesive compositions and the easy-adhesive films tended to increase as the emulsion particle size increased. Comparative Example 6 (easy-adhesive composition 7) using a crosslinked water-based polyurethane had poor solution stability and insufficient adhesion between the easy-adhesive film and the polarizer.
[0141] The above results show that by using a solution of an aqueous polyurethane having a small emulsion particle size, an easily adhesive film having low haze, excellent transparency, and high adhesive strength to an adherend such as a polarizer can be obtained.
Claims
1. A method for producing an easy-adhesive film, wherein the easy-adhesive film comprises an easy-adhesive layer on a surface of a transparent film substrate, the method comprising: a step of coating the easily adhesive composition on the transparent film substrate, and a step of heating the easy-adhesion composition to remove the solvent, The easy-adhesion composition is an aqueous solution containing water-based polyurethane, The particle size of the aqueous polyurethane emulsion is less than 30 nm.
2. The method for producing an easy-adhesion film according to claim 1, wherein: The water-based polyurethane is a polyurethane without a cross-linking structure. The easy-adhesion composition further includes a cross-linking agent capable of cross-linking with the water-based polyurethane.
3. The method for producing an easily adhesive film according to claim 1 or 2, wherein: In the step of removing the solvent, the transparent film substrate coated with the easily adhesive composition is stretched in at least one direction while being heated.
4. The method for producing an easily adhesive film according to claim 1 or 2, wherein: The easy-bonding composition further comprises microparticles.
5. The method for producing an easily adhesive film according to claim 1 or 2, wherein: The thickness of the easy-adhesion layer is greater than 110 nm.
6. The method for producing an easily adhesive film according to claim 1 or 2, wherein: The transparent film substrate is an acrylic film.
Citation Information
Patent Citations
Production and use of clear heat-resistant resin
JP2000230016A
Method of manufacturing for transparent heat resistant resin and use of the same
JP2001151814A
Transparent thermoplastic resin laminate
JP2002120326A
Thermoplastic resin laminate
JP2002254544A
Lactone ring-containing polymer, and its manufacturing method and application
JP2005146084A